"Ad lucem-- towards the light" : a comparison of two principals at Napier Girls' High School, Miss B. Spencer, 1901-1909 and Miss R. James, 1969-1989 : a thesis in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Medcalf, Pam (Massey University, 2005)
The aim of this thesis is to compare and contrast the early life and teaching, principalships and community involvement of two principals at a girls' state secondary school in Napier, Napier Girls' High School (NGHS). Miss B Spencer Lady Principal 1901 - 1909 and Miss R James Principal 1969 - 1989 They were chosen because they were not only successful in their time at NGHS but in their community involvement gaining the award of O.B.E. - Miss James for her services to education and the community and Miss B. Spencer for her efforts in introducing the Country Women's Institutes to New Zealand The focus will be on their leadership qualities, motivation, interests and achievements but will also include their influence on the school, the functioning of the school and the problems they faced in the different time periods and their community involvement. To provide a background there will be a brief survey of education in New Zealand and Britain at the time of both principals and some comparison between NGHS and Nelson College for Girls (NCG) Miss R. James was a student at NCG and it is a state girls ' secondary school with a boarding establishment founded the year before NGHS and very similar. There was no comparable school in Hawke's Bay or Poverty Bay.
Keywords: Spencer, Bessie; James, Rosemary, 1935-1990; Women school principals; New Zealand -- Napier